Perceptions and Experiences of Overweight among Women in the Ga East District, Ghana - Aryeetey, Richmond Nii Okai (Frontiers in Nutrition, 2016)
Introduction: Overweight and obesity are a growing public health challenge among women of reproductive age. While cultural norms suggest preference for an overweight body image, limited evidence exists regarding women’s beliefs and experiences of overweight in Ghana. The current study explored beliefs, perceptions, experiences and practices concerning overweight among women living in suburban Accra, Ghana. Methods: Four focus group discussions, and 10 in-depth interviews (IDI) were implemented among 42 adult women (>18y) seeking preventive child health services in Dome, Accra. All the women in the IDI were overweight. In addition to notes, interviews and discussions were audio-recorded and transcribed for systematic content and narrative analysis. Results: Overweight was considered undesirable by most women. Overweight individuals were often stigmatized using uncomplimentary names like cargo, obolo, etc. However, some weight gain was admired and expected by women and their family and friends. Weight gain that was considered beautiful was believed to ‘evolve naturally’. Weight gain that is either medically-induced perceived as excessive, was not viewed positively. Weight gain by women was perceived as a sign of financial prosperity and good care by a spouse. Overweight was perceived to be linked with heredity, childbirth, gluttony, and contraception. Adverse experiences of overweight included poor self-image, declining social lifestyle, increased disease risk, and feeling tired always. Strategies which had been used in order to lose weight included skipping meals, avoiding carbohydrate-based foods, and drinking herbal teas. Conclusion: There is admiration for some weight gain among women but when it is excessive, overweight is stigmatized. Misperceptions regarding partner expectations, determinants of overweight, and weight reduction strategies requires effective behavior change interventions in Ghana.